Repair of Ultraviolet Radiation Damage in Sensitive Mutants of Micrococcus radiodurans - Moseley, B. E. B. (1969)
Various aspects of the repair of ultraviolet (UV) radiation-induced damage were compared in wild-type Micrococcus radiodurans and two UV-sensitive mutants. Unlike the wild type, the mutants are more sensitive to radiation at 265 nm than at 280 nm. The delay in deoxyribonucleic acid (DNA) synthesis following exposure to UV is about seven times as long in the mutants as in the wild type. All three strains excise UV-induced pyrimidine dimers from their DNA, although the rate at which cytosine-thymine dimers are excised is slower in the mutants. The three strains also mend the single-strand breaks that appear in the irradiated DNA as a result of dimer excision, although the process is less efficient in the mutants. It is suggested that the increased sensitivity of the mutants to UV radiation may be caused by a partial defect in the second step of dimer excision.